Gene transfer and expression protocols - Murray, E. J (Humana Press, 1991)
Roche Products Ltd, Welwyn Garden City, Hertfordshire, U.K.. Techniques for introducing an isolated gene into a cell line using a variety of transfection techniques. For final year graduate students, postgraduates, or postdoctorate scientists in gene regulation research.
Methods in molecular biology ; vol. 7
Keywords: Genes; exprese genu; Geny; Gene Expression; Gene Transfer Techniques; geny; transfer faktor; Transfer Factor; biologie; genetika, lékařská genetika; Molecular Biology; molekulární biologie; technika přenosu genů